Natural bioactive compounds as adjuvant therapy for hepatitis c infection - Santana, Moema S. [UNESP]; Lopes, Rute [UNESP]; Peron, Isabela H. [UNESP]; Cruz, Carla R. [UNESP]; Gaspar, Ana M. M. [UNESP]; Costa, Paulo I. [UNESP] (Bentham Science Publishers, 2021)
Background: Hepatitis C virus infection is a significant global health burden, which causes acute or chronic hepatitis. Acute hepatitis C is generally asymptomatic and progresses to cure, while persistent infection can progress to chronic liver disease and extrahepatic manifestations. Standard treatment is expensive, poorly tolerated, and has variable sustained virologic responses amongst the different viral genotypes. New therapies involve direct acting antivirals; however, it is also very expensive and may not be accessible for all patients worldwide. In order to provide a complementary approach to the already existing therapies, natural bioactive compounds are investigated as to their several biologic activities, such as direct antiviral properties against hepatitis C, and effects on mitigating chronic progression of the disease, which include hepatoprotective, antioxidant, anticarcinogenic and anti-inflammatory activities; additionally, these compounds present advantages, as chemical diversity, low cost of production and milder or inexistent side effects. Objective: To present a broad perspective on hepatitis C infection, the chronic disease, and natural compounds with promising anti-HCV activity. Methods: This review consists of a systematic review study about the natural bioactive compounds as a potential therapy for hepatitis C infection. Results: The quest for natural products has yielded compounds with biologic activity, including viral replication inhibition in vitro, demonstrating antiviral activity against hepatitis C. Conclusion: One of the greatest advantages of using natural molecules from plant extracts is the low cost of production, not requiring chemical synthesis, which can lead to less expensive therapies available to low and middle-income countries.
Keywords: Adjuvant therapy; Hepatitis; Hepatitis C virus; Molecular pathways; Natural bioactive compounds; Viral replication